The Effect Of Covid-19 On The Occurrence Of All Star Hotels On The Island Of Java-Bali During The Pandemic - Diva Wahyu Syaputri Diva; Nurafni Elvitia; Nur Indah Riwajanti (Yayasan Riset dan Pengembangan Intelektual, 2021)
Covid-19 is an epidemic that is sweeping across the country right now. The community is greatly affected by this pandemic, especially in the tourism sector, from flights to hotels which are usually crowded with visitors from outside the region and from abroad. Until now, the government is still trying to get the Covid-19 virus to immediately break the chain. The purpose of this analysis is to find out how the influence of Covid-19 on hotel occupancy rates on the islands of Java and Bali. The research sample was obtained from the Central Statistics Agency (BPS). The analysis technique in this study uses regression analysis. From the results of the analysis, it can be seen that there are significant changes in hotel occupancy rates from before and during Covid19. Thus showing that Covid12 has an effect on the hotel economy.